After the Retrospective: Bergman's Winter Light - Tomić, Janica (Array, 2014)
The first instalment in Ingmar Bergman’s "Trilogy", Winter Light (Nattvardsgästerna, 1962) begins with a long sequence of a lecture held by a provincial pastor, the film’s protagonist, before a sparse and disinterested crowd of churchgoers. A depressed fisherman confesses he is haunted by newspaper headlines on the threat of a Chinese invasion and a bundle of fears which the pastor fails to alleviate. In Bergman studies the "Triology" traditionally marks different moments of crises: the new wave of "anti-Bergman" or "political film" was under way in Sweden, Bergman would soon state that the critics had successfully turned him into a "dinosaur", ready to be confined to realms of film cannon and archive ; 1963. is also a turning point in Swedish film history. Furthermore, readings of Winter Light drew upon Bergman's own parallels with his father’s disillusionment in his role as a priest (as described almost obsessively in The Best Intentions, Sunday’s Children, Lanterna Magica, etc), and its reflection in Bergman’s own crises of faith in the role of artist (as described in e.g. parable on Cathedral in Chartres). So, although Bergman was prolific in self-fashioning and produced reflections on his life and work in different media throughout his career, Winter Light has come to define his biography and work for generations of readings, such as V. Sjöman's documentary Ingmar Bergman makes a movie (Ingmar Bergman gör en film, 1967), A. Ahndoril's biography Director (Regissören, 2006), M. Cousin’s The Story of film (2011), etc. This paper discusses this interest in Winter Light and other possible appropriations (Buden and Žilnik: Uvod u prošlost, 2014).